1985
DOI: 10.1515/znb-1985-1203
|View full text |Cite
|
Sign up to set email alerts
|

PNP-Perthionitrit und PNP-Monothionitrit / PNP-Perthionitrite and PNP-M onothionitrite

Abstract: Abstract As a major product from the reaction of PNP-nitrite [P = P(C6H5)3] with elementary sulfur or a PNP-polysulfide (PNP)2S12 in acetone under anaerobic conditions PNP-perthionitrite (PNPnitrosodisulfide) PNP-SSNO has been isolated. VIS/UV-spectra point to a thionitrate or perthionitrate as a precursor. The structures of PNP-SSNO and of the product obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 1 publication
4
77
1
Order By: Relevance
“…Compared with previous reports [285,286], this spectrum was assigned to a hydrodisulfide ONSSH/ONSS − [284]. One speculated mechanism involves an initial nucleophilic attack of H 2 S on RSNO forming HSNO/ − SNO (eq.…”
Section: H2s Reaction With Thiol Derivatives (Or Thiol Reaction Wimentioning
confidence: 61%
“…Compared with previous reports [285,286], this spectrum was assigned to a hydrodisulfide ONSSH/ONSS − [284]. One speculated mechanism involves an initial nucleophilic attack of H 2 S on RSNO forming HSNO/ − SNO (eq.…”
Section: H2s Reaction With Thiol Derivatives (Or Thiol Reaction Wimentioning
confidence: 61%
“…When studying the reaction of S-nitrosoglutathione with H 2 S, at pH 7.4 we observed the formation of yellow product with absorbance at 412 nm but because the time-resolved 15 N NMR studies and time-resolved IR studies confirmed that the 15 N NMR signal and N ¼ O vibrational band, respectively, were only present for short amount of time, while the 'yellow' product remained stable for couple of hours (slowly decaying with sulfur precipitation), we proposed that this is a mixture of polysulfides/sulfur sols [13,36]. Working with pure SSNO 2 we could not test whether there was a water-induced hypsochromic shift, as PNP þ SSNO 2 , as in the Seel's report [32], decomposed when 10% of water was added into the acetone solution of the salt [36]. The matured mixture of GSNO and H 2 S, called 'SSNO 2 mix', has been referred to as enriched SSNO 2 in several papers [35,40 -42], solely based on 412 nm absorbance, although no real chemical evidence was provided to prove that this 'yellow' mixture consists of SSNO 2 .…”
Section: Uv/vis Spectral Properties Of Ssno 2 In Watermentioning
confidence: 88%
“…A versatile approach to the preparation of salts of binary S,N and ternary S,N,O anions in high yields entails the reactions of silylated derivatives with potassium t-butoxide in ether solvents such as tetrahydrofuran (THF) or boiling dimethoxyethane (DME), as exemplified by the high-yield syntheses of K [NSO] and K2 [NSN] reported by Armitage and Herberhold, respectively; 1, 2 this process is favoured by the formation of the strong Si-O bond in the Me3SiO t Bu by-product [eqn (1) and 2]. Other alkali-metal salts M[NSO] (M = Na, Rb, Cs) have also been prepared by the method shown in eqn (1), 18 while Mews accomplished the synthesis of the soluble tris(dimethylamino)sulfonium (TAS) salt in liquid SO2; the latter transformation is driven by the elimination of volatile trimethylsilyl fluoride [eqn (3)]. 19 KO t Bu + Me3SiNSO…”
Section: Binary Sn and Ternary Sno Anionsmentioning
confidence: 99%
“…For example, Seel demonstrated that the red anion SSNOanion is produced by the reaction of an ionic nitrite such as KNO2 with elemental sulfur or a polysulfide in acetone, dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) and can be isolated as the PPN + salt (Section 4). 3 Thirty years later Filipovic et al re-investigated this synthesis using K 15 NO2, which allows monitoring the progress of the reaction by 15 N NMR spectroscopy (Section 3.1). A resonance at -67 ppm (cf.…”
Section: Binary Sn and Ternary Sno Anionsmentioning
confidence: 99%